Towards Ontological Approach on Trust-Aware Ambient Services - O-Joun Lee; Hoang Long Nguyen; Jai E. Jung; Tai-Won Um; Hyun-Woo Lee (IEEE Access)
With various information sources (e.g., from IoT sensors to social media), it is difficult to provide users with trustworthy services in ambient environment. The aim of this paper is $i$ ) to design trust ontology for representing semantics of the ambient services and $ii$ ) to compute trust measures among users by using a personalized trust ontology. In particular, given a large amount of data collected from ambient sensors, efficient trust computation and reasoning are required for the stability and reliability. Thereby, we propose trust ontology-based framework for deriving personalized ontologies for individual users according to their preference, perspective, and purpose. To evaluate the proposed model, we have figured out a method how the degree of trust is estimated based on the trust ontology. Furthermore, we have proved that the proposed method is reliable with a case study on a social media (Twitter) for a particular domain (restaurant).